PD-L1 is remarkably over-expressed in EBV-associated pulmonary lymphoepithelioma-like carcinoma and related to poor disease-free survival - Wenfeng Fang; Shaodong Hong; Nan Chen; Xiaobo He; Jianhua Zhan; Tao Qin; Ting Zhou; Zhihuang Hu; Yuxiang Ma; Yuanyuan Zhao; Ying Tian; Yunpeng Yang; et al. (2015)
// Wenfeng Fang 1, 2, * , Shaodong Hong 1, 2, * , Nan Chen 3, * , Xiaobo He 3 , Jianhua Zhan 1, 2 , Tao Qin 1, 2 , Ting Zhou 1, 2 , Zhihuang Hu 1, 2 , Yuxiang Ma 1, 2 , Yuanyuan Zhao 1, 2 , Ying Tian 1, 2 , Yunpeng Yang 1, 2 , Cong Xue 1, 2 , Yanna Tang 3 , Yan Huang 1, 2 , Hongyun Zhao 1, 2 , Li Zhang 1, 2 1 State Key laboratory of Oncology in South China, Department of Medical Oncology, Sun Yat-Sen University Cancer Center, Guangzhou, P. R. China 2 Collaborative Innovation Center for Cancer Medicine, Sun Yat-sen University Cancer Center, Guangzhou, Guangdong, China 3 Department of Oncology, the Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong, China * These authors have contributed equally to this work Correspondence to: Li Zhang, e-mail: zhangli@sysucc.org.cn Keywords: pulmonary lymphoepithelioma-like carcinoma, PD-L1, Epstein–Barr virus Received: May 07, 2015      Accepted: August 14, 2015      Published: August 24, 2015 ABSTRACT Backgroud: Programmed cell death-ligand 1 (PD-L1) and driver mutations are commonly seen in non-small-cell lung cancer (NSCLC). However, the prevelance of PD-L1 over-expression and its prognostic value in Epstein–Barr virus (EBV) associated pulmonary lymphoepithelioma-like carcinoma (LELC) remains poorly understood. Methods: A total of 214 NSCLC patients and 113 surgically treated pulmonary LELC patients were included. Paraffin-embedded tumor sections were stained with PD-L1 antibody. Correlations between PD-L1 expression and clinicopathological features as well as survival outcomes were analyzed. Results: The frequency of PD-L1 over-expression in NSCLC was 51.4%. No significant association was observed between common driver mutations and PD-L1 over-expression. Remakably, the positive rate of PD-L1 in pulmonary LELC was 74.3%. High PD-L1 expression was associated with impaired diseas-free survival (DFS) compared with low PD-L1 expression ( p = 0.008). Multivariate analysis shows that PD-L1 expression level, N stage and M stage were independent prognostic factors for DFS. N stage and M stage but not PD-L1 expression level were significantly associated with overall survival (OS). Conclusions: PD-L1 over-expression was not related to common driver mutations in NSCLC. Pulmonary LELC have remarkably high incidence of PD-L1 expression. PD-L1 was a negative prognostic factor for DFS in surgically resected pulmonary LELC. These findings may provide a rationale for immunotarget therapy in this virus-associated lung cancer.